Dimensi Estetika dan Identitas Budaya dalam Bangunan Keraton Surakarta - Muhadiyatiningsih, Siti Nurlaili; Fathonah, Siti (FIKRAH, 2020)
Karaton Kasunanan Surakarta is one of the important historic sites in the spread procces of Islam in java. Acculturation between several aspects that manifested in building are symbols full of meaning that is interesting to discuss. This article wants to discuss about the aesthetic dimensions and cultural identity stored in the Surakarta Kasunanan palace building. Through symbol theory and identity, the interim findings in this paper are firstly the aesthetics and cultural identity which are much associated with beauty in Javanese terminology cannot be separated from being appropriate, inappropriate, and beautiful, not beautiful. Secondly, in the context of identity, there are stored messages that represent Islamic teachings and Javanese-European culture. As for the whole, the structure of the building in the palace of the Surakarta Sunanate keeps the symbolic meaning of human purification into a human being through several ways in the teachings of Tariqah.